Understanding the demotic film critic - Nathan, Matthew (2019)
This paper is concerned with a subsection of film critic on YouTube, referred to within this thesis as a film reviewer. Across two years, this thesis details an investigation into film reviewers analyzing the content of four YouTube channels. The purpose of this is to understand how film reviewers contribute to film culture by creating a demotic pathway into it for the layman. Within the investigation, the four YouTubers chosen all had over 100,000 subscribers and all conformed to a set of standardized norms that define them as film reviewers. During the investigation, these channels had the entirety of their video libraries examined so as to discern initially the form of film reviewing. As well as qualitatively reading the videos, the language was studied quantitively through utilizing of a language reading service to prove that film reviewers do speak in a more understandable way than other kinds of film critic. The investigation then progressed onwards to understanding how the method of film reviewing has the potential to impact its audience. Film reviewing is a primarily demotic practice that opens up conversations for layperson cinemagoers. The analysis demonstrated that reviewers are able to engage viewers in discourse around cinema through multiple tactics. Finally, this paper aims begin research around film reviewers, with the aim that they be investigated in further depth.